Peran Bantuan Hukum Struktural dalam Transformasi Sosial: Sebuah Upaya Mewujudkan Kesetaraan Gender dan Perubahan Struktur dalam Masyarakat - Ningtyas, Dyah Palupi Ayu; Al Uyun, Dhia; Susmayanti, Riana (Law and Human Rights Research and Development Agency, 2023)
Structure-oriented or system-oriented movements will be more advanced than ordinary movements without relying on a system (normative). Structural legal aid is included in the movement of non-governmental organizations whose work system leads to structural or systemic changes, rather than changes at the individual or case-by-case level. The legal aid movement aims to ensure access to justice for people in need, especially women. With normative legal research, it is hoped that this can provide important findings about community colaboration, aid service providers, NGOs, and CSOs in societal change and equality. Thus, structural legal aid is a legal aid strategy based on the movement by eliminating power relations and gender inequality. In addition, village women paralegals can act as a movement to realize structural gender legal assistance for women, children, and other marginalized groups, and not just for the poor. The old perspective on traditional legal aid is not effective, makes structural legal aid an alternative from legal aid, that can be encouraged by movement that can eliminate gender inequality and change existing structures in society. Women’s participation as paralegals in a social movement can be optimized with support from NGOs and CSOs such as legal aid organizations. So that women’s social movements produce gender equality, fulfill women’s rights, and overcome discrimination. Apart from that, the legal aid movement needs to be focused and structured so that women’s rights are fulfilled. The challenge for paralegals is to be able to go beyond the duits stated in the UUBH.